Faktor psikologis dan peran literasi keuangan dalam keputusan investasi cryptocurrency gen-z - Gunanto, Dedi; Kusuma, Pradana Jati (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
This study was conducted to analyze the influence of psychological herding behavior and illusion of control on cryptocurrency investment decisions with financial literacy as moderation. This research focuses on generation z in Semarang City, which often faces difficulties in making investment decisions due to psychological factors and different levels of financial literacy. The sample selection used purposive sampling technique, with a total sample of 130 respondents. The results showed that herding behavior and illusion of control positively and significantly affect cryptocurrency investment decisions, indicating that young investors tend to follow market trends and have excessive confidence in their abilities. However, financial literacy was unable to moderate the relationship, suggesting that current financial knowledge is not enough to reduce psychological biases in investment decision-making. These findings underscore the importance of improving financial literacy among Generation Z so that they can manage their investment portfolios more wisely, especially in the face of investment instruments that have the potential for high returns but also great risks.